Remedial Effect of Intravenous Cyclophosphamide in Corticosteroid-Refractory Patients in the Acute Phase of Neuromyelitis Optica Spectrum Disorder-Related Optic Neuritis - Wang, Ling; Liu, Kaiqun; Tan, Xiao; Zhou, Lin; Zhang, Yuxin; Liu, Xiaoning; Fu, Yue; Qiu, Wei; Yang, Hui (Frontiers in Neurology, 2021)
Background: To investigate the remedial efficacy and safety of intravenous cyclophosphamide (CP) in the acute phase in patients with neuromyelitis optica spectrum disorder-related optic neuritis (NMOSD-ON) who are refractory to intravenous methylprednisolone (MP) treatment. Design: This study was a single-center, retrospective, observational case-control cohort study. Methods: Thirty-six patients who had acute NMOSD-ON attacks and were refractory to MP treatment were included. Patents were divided into two groups: the remedial CP group, and the MP group. The best-corrected visual acuity (BCVA), mean deviation (MD) of the visual field (VF), visual evoked potential amplitude (VEP-A), visual evoked potential latency (VEP-T), and average thickness of the retinal nerve fiber layer (RNFL) at onset, 1 month (m), 3 m, and 6 m after the attack were analyzed. Routine blood test results, liver and kidney function, routine urinalysis results and general condition were analyzed for safety issues at each follow-up. Fisher's exact test, the Mann-Whitney U test, the Kruskal-Wallis test and the Wilcoxon rank-sum test were used for statistical analysis. Results : The remedial CP group showed significant improvement over 6m with regard to BCVA and MD(P<0.05),whereas MP group only showed significant improvement in MD (P＜0.05). Regarding remedial CP intervention time window, the CP≤30 days group showed significant improvement over 6 m with regard to BCVA (P=0.002), MD (P=0.003), and VEP-A (P=0.036), while those CP >30 days group did not. Both the remedial CP group and the MP group showed significantly RNFL thickness reduction, however, BCVA, MD, VEP-A, VEP-T and RNFL thickness showed no significant differences between the two subgroups at any follow-up point (P>0.05). Conclusion: CP within 30 days of attack onset is safe and might have a beneficial degree of therapeutic efficacy for acute-phase treatment of NMOSD-ON that is refractory to MP treatment alone.